2019
DOI: 10.1111/glob.12237
|View full text |Cite
|
Sign up to set email alerts
|

Traceability in global governance

Abstract: An increasingly important challenge in global governance, which in some issue areas has been labelled ‘traceability’, has been to track the cross‐border travels of objects that are associated with positive or negative effects. However, the common properties and identifiable patterns of variation of traceability across issue areas or industries have been insufficiently explored. We identify key properties of traceability systems, including the variation and interactions between the physical properties of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…On the one hand, the level of concentration of deposits affects traceability: it is much easier to trace the provenance of minerals if deposits are concentrated in a few countries. On the other hand, geological particularities and the chemical composition of minerals can impact the ability to trace minerals (Muirhead & Porter, 2019). For instance, some minerals can only be extracted via large scale, industrial mining.…”
Section: Industry Characteristicsmentioning
confidence: 99%
“…On the one hand, the level of concentration of deposits affects traceability: it is much easier to trace the provenance of minerals if deposits are concentrated in a few countries. On the other hand, geological particularities and the chemical composition of minerals can impact the ability to trace minerals (Muirhead & Porter, 2019). For instance, some minerals can only be extracted via large scale, industrial mining.…”
Section: Industry Characteristicsmentioning
confidence: 99%
“…As we know from research on bribery, intermediate structures or per sons are of critical importance for the organisation of illegal/legal proce dures and the "transformation" of the status of goods. The supply chain literature has shown that intermediate structures such as smelters for raw materials or sawmills in the illicit trade of wood are essential points where transparency and traceability will come to a chokepoint and even to a rapid stop (Muirhead and Porter 2019). So these points in a supply chain are of major concern in the tracking of illicit proceeds and of the partici pants in those stages of the supply chain.…”
Section: Places and Nodesmentioning
confidence: 99%
“…La tercera opción y también la que puede generar más reticencias institucionales, tiene que ver con la mejora en la transparencia del proceso y gestión de estos casos, ya que permitiría un mayor control en la aplicación de la ley por los operadores jurídicos y en el cumplimento de los requisitos propios del proceso penal en el que está inmerso el caso (Muirhead & Porter, 2019). La trazabilidad no solo permite identificar los cambios ocasionados en el objeto a lo largo de su trayectoria, sino que también es posible verificar la efectiva aplicación de controles o normas externas en cada una de las fases.…”
Section: Posibles Aplicaciones En La Investigación Criminológicaunclassified